👤

Answer :

Answer:

[tex]\frac{1}{n^{18}} = (n^{-3})^6[/tex]

Step-by-step explanation:

Given

[tex]\frac{1}{n^{18}}[/tex]

Required

Determine its equivalent

[tex]\frac{1}{n^{18}}[/tex]

Express 18 as 3 * 6

[tex]\frac{1}{n^{18}} = \frac{1}{(n^{3})^6}[/tex]

This can be rewritten as:

[tex]\frac{1}{n^{18}} = (\frac{1}{n^{3}})^6[/tex]

Apply the following law of indices:'

[tex]\frac{1}{a^b} = a^{-b}[/tex]

[tex]\frac{1}{n^{18}} = (n^{-3})^6[/tex]

Hence;

(d) is correct

Answer:D

Step-by-step explanation: cause im big brain